2024
DOI: 10.1037/rev0000450
|View full text |Cite
|
Sign up to set email alerts
|

The violation-of-expectation paradigm: A conceptual overview.

Francesco Margoni,
Luca Surian,
Renée Baillargeon

Abstract: For over 35 years, the violation-of-expectation paradigm has been used to study the development of expectations in the first 3 years of life. A wide range of expectations has been examined, including physical, psychological, sociomoral, biological, numerical, statistical, probabilistic, and linguistic expectations. Surprisingly, despite the paradigm's widespread use and the many seminal findings it has contributed to psychological science, so far no one has tried to provide a detailed and in-depth conceptual o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 248 publications
0
3
0
Order By: Relevance
“…They recognize agents' intentions and goals, looking longer when agents change their goals or act inefficiently Luo & Baillargeon, 2005;Woodward, 1998). For reviews and meta-analyses of this literature, see: Carey (2009); Kunin et al (2023); Liu and Almeida (2023); Margoni et al (2023);. These expectations persist throughout our lives, guiding the judgments, predictions, and explanations of adults (Gao et al, 2009;Scholl, 2001;Scholl & Tremoulet, 2000;Shu et al, 2021;Smith et al, 2020).…”
Section: Evidence From Development: Infants Have Domain-specific Expe...mentioning
confidence: 99%
“…They recognize agents' intentions and goals, looking longer when agents change their goals or act inefficiently Luo & Baillargeon, 2005;Woodward, 1998). For reviews and meta-analyses of this literature, see: Carey (2009); Kunin et al (2023); Liu and Almeida (2023); Margoni et al (2023);. These expectations persist throughout our lives, guiding the judgments, predictions, and explanations of adults (Gao et al, 2009;Scholl, 2001;Scholl & Tremoulet, 2000;Shu et al, 2021;Smith et al, 2020).…”
Section: Evidence From Development: Infants Have Domain-specific Expe...mentioning
confidence: 99%
“…Increased looking toward the object associated with the word or the action cue is interpreted as evidence of infants having learned the word-object or actionobject association, see Table 1. Given limited evidence of learning in the preferential looking task in Eiteljörge et al ( 2019), we also included a VoE task (see Margoni et al, 2023 for a recent review) following the preferential looking task. Here, children were presented with matching trials where they were shown an object paired with a corresponding word or action cue that they had seen during training.…”
Section: The Current Studymentioning
confidence: 99%
“…an agent behaves inefficiently) relative to visually similar but expected events [1][2][3] . Longer looking at these surprising events, or the violation-of-expectation (VOE) effect, is taken as evidence for a hypothesised expectation held in infants' minds 4 : e.g. that unsupported objects fall, and that agents tend to act efficiently [5][6][7][8] .…”
Section: Main Textmentioning
confidence: 99%